Evaluation of Electrophysiological Effects of Melatonin and Alpha Lipoic Acid in Rats with Streptozotocine Induced Diabetic Neuropathy - Seyit, D. A.; Degirmenci, E.; Oguzhanoglu, A. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Introduction: Neuropathy is a common complication of diabetes mellitus and is closely related to quality of life. There are many studies in which biological ingredients, such as alpha lipoic acid (ALA), that may inhibit or reduce the generation of diabetic neuropathy were investigated. Another biological agent that may reduce the generation of diabetic neuropathy is melatonin and there are a few studies that investigate the effects of melatonin on diabetic neuropathy. In this study we aimed to examine the effect of melatonin on experimentally induced diabetic neuropathy by comparing it with both ALA and control groups.Methods: We included 24 male Wistar rats. Tibial motor nerve conduction and cortical tibial nerve somatosensory evoked potentials (SEP) studies were performed before and after diabetes mellitus (DM) for all rats. Rats were divided into 3 (ALA, melatonin and control) groups. After 2 weeks of treatment period, tibial motor nerve conduction and cortical tibial SEP studies were repeated.Results: Our data showed that ALA significantly increased nerve conduction velocity and amplitude in rats with diabetic neuropathy (p=0,001; p=0,002). Also, melatonin significantly increased nerve conduction velocity and amplitude in rats with diabetic neuropathy (p=0.002; p=0.002). There was no significant difference between the electrophysiological effects of ALA and melatonin. Besides, neither ALA nor melatonin did significantly affect P1 and N1 latency values on cortical tibial nerve SEP studies.Conclusion: Our study is the study in which both tibial nerve conduction and cortical tibial SEP studies were performed to compare effects of ALA and melatonin on experimental diabetic neuropathy. Lack of significant difference on cortical tibial SEP study would be attributed to the involvement of other central nervous system pathways which do not include ALA or melatonin in the pathogenesis. Results of ALA group are important by means of giving objective evidences for results of biochemical studies about the role of ALA in the pathogenesis of diabetic neuropathy. However, there is not enough information about the effect of melatonin in the pathogenesis of diabetic neuropathy. Consequently, results of our study may anticipate further biochemical and clinic studies which investigate the about the role of melatonin in diabetic neuropathy.
Keywords: alpha lipoic acid; melatonin; diabetic neuropathy